Efektivitas Model Latihan High Intensity Interval Training untuk Meningkatkan Kecepatan Berenang Gaya Bebas 50 Meter - Kurniawan, Wing Prasetya (MAN Insan Cendekia Jambi, 2025)
The effectiveness and quality of swimmers' physical performance ultimately depend on the determination of training zones, energy requirements, and the distance to be targeted as chosen by the swimmers. Physiological adaptations such as aerobic and anaerobic performance are key factors in improving the performance of swimming athletes. The purpose of this study was to determine how high-intensity interval training affects the speed of the 50-metre freestyle swim. This study was designed as a quasi-experimental study with a pretest-posttest design. Both the population and sample were selected using purposive sampling from 16 swimmers at the Sailfish Swimming Club. The t-test formula was used for data analysis. According to the pre- and post-test results, the results were significant at the 0.000 < 0.05 level, with an average pre-test time of 46.36 seconds and an average post-test time of 42.20 seconds.